(untitled) (Diversity Research: Journal of Analysis and Trends, 2023)
to determine the value of ultrasound examination (ultrasound) in the diagnosis of early destructive changes in the joints of the hands and the rate of progression of rheumatoid arthritis (RA) in patients with different ages of disease onset.